NiCo composite catalysts for CO2 methanation: the effect of preparation methods on catalyst structure and activity. (6th April 2023) - Deng, Lidan; Tan, Yuhang; Chen, Chong; Li, Fukun; Zhang, Xianming
Abstract : Ni–Co alloy catalysts with spherical clusters or a developed bimodal mesoporous structure feature higher activities for CO2 methanation. Abstract : The tuning of catalyst structures is a significant strategy to produce highly active catalysts. Five primary methods were used herein to prepare NiCo composite catalysts, which were named NiCo-SG (sol– gel method), NiCo-PC (precipitation method), NiCo-WT (hydrothermal method), NiCo-ST (soft template method), and NiCo-HT (hard template method). Characterization indicated that there were different surface and bulk properties for these catalysts. Activity evaluation was subsequently conducted using CO2 methanation as a probe reaction. The results showed that the activity of CO2 methanation on the catalyst was positively correlated with the absorption of CO2, and with high CO2 methanation for NiCo-ST and NiCo-HT: the highest CH4 formation rates were 4.55 and 4.56 × 10 −5 mol gcat −1 s −1, respectively. This was attributed to the Ni–Co alloy and spherical clusters of the former and the large specific surface area and developed bimodal mesoporous structure of the latter.